Chemotherapy for breast cancer progresses to liver metastases after surgery and systemic treatment - Yin, Tao; Nie, Lei; Wu, Dongde; Liu, Baozhen; Feng, Yaojun; Wu, Xinhong; Luo, Chenggang; Liang, Jianjun (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2020)
Background: This study aims to evaluate the effectiveness of hepatic arterial infusion chemotherapy/portal vein infusion chemotherapy (HAIC/PVIC), transcatheter hepatic arterial chemoembolization (TACE) and transcatheter arterial embolization (TAE) for unresectable breast cancer liver metastases (UBCLM). Methods: The present study included 57 patients. These patients were randomly divided into three groups (n=19, each): HAIC/PVIC group, TACE group and TAE group. Patients in the HAIC/PVIC group were treated with the same systemic chemotherapy regimen previously received by infusion through an intra- arterial and portal vein catheter. Patients in the TACE group received cyclophosphamide, epirubicin and 5-fluorouracil, and embolization. Patients in the TAE group were only treated with embolization. Results: The median number of treatments was 6 (range, 3–13) in the HAIC/PVIC group, 5 (range, 4–9) in the TACE group, and 6 (range, 4–8) in the TAE group. The 1-, 2- and 3-year survival rates for these groups were 18/19 (94.7%), 14/19 (73.7%) and 11/19 (57.9%), 14/19 (73.7%), 9/19 (47.4%) and 8/19 (42.1%), and 8/19 (42.1%), 4/19 (21.1%) and 0/19 (0%), respectively. The median overall survival from the original breast cancer diagnosis was 88 (range, 11–133), 75 (range, 9–115), and 49 (range, 10–64) months in the HAIC/PVIC, TACE and TAE groups, respectively. Grade I–II and grade III–IV bone marrow suppression was observed in 12/19 (63.2%) and 3/19 (15.8%) patients in the HAIC/PVIC group, respectively, in 17/19 (89.5%) and 5/19 (26.3%) patients in the TACE group, respectively, and in 0/19 (0%) and 0/19 (0%) patients in the TAE group, respectively. Conclusions: HAIC/PVIC with the same regional chemotherapy regimen of the original systemic treatment is feasible, and can benefit patients with UBCLM, who have progressed on prior systemic therapies.